Deletion of the CYP2D6 gene as a likely explanation for the serious side effects of the antipsychotic drug pimozide: a case report - Facal, Fernando; Portela, Begoña; Gil-Rodríguez, Almudena; Barros, Francisco; Maroñas, Olalla; Carracedo, Angel (Frontiers in Pharmacology, 2023)
CYP2D6 analysis prior prescription of pimozide is required above a certain dose by the Food and Drug Administration in order to detect individuals with poor metabolizer status. This precautionary measure aims to prevent the occurrence of serious adverse drug reactions. A case of a patient with a diagnosis of schizophrenia spectrum disorder is presented. The patient suffered re-admission in the psychiatry ward because of severe secondary symptoms to the antipsychotic drug pimozide, previously prescribed on a first admission. In order to assess the patient's medication profile, realtime PCR was performed to analyse the main genes responsible for its metabolisation, namely CYP2D6 and CYP3A4. The pharmacogenetic study revealed that the patient is a poor metabolizer for CYP2D6, presenting deletion of both copies of the gene (diplotype *5/*5). Fortunately, the symptomatology disappeared after the withdrawal of the responsible drug. In conclusion, the follow-up of pharmacogenetic clinical practice guidelines and therefore the pharmacogenetic analysis of CYP2D6 when prescribing pimozide would probably have saved the severe side effects, avoiding consequences for the patient and the health system expenditure. There is an important need for more training in the pharmacogenetics field for specialists in psychiatry.